The Application of Scaffolding Instruction Mode to English Writing Teaching in Primary School——A Case Study of ML Primary School in GZ City - Dong, Lirong; Huang, Zhenhui (Communication & Education Review, 2023)
English writing is a very important part of the whole English learning process. However, at present, primary school students’ writing level and interest in English writing is low. This study applied Scaffolding Instruction mode to English writing teaching in the fourth grade of primary school, and carried out a 16-week teaching experiment, by means of questionnaire and test, using SPSS 22.0 software to compare and analyze students’ writing score and interest before and after the experiment, so as to explore the influence of Scaffolding Instruction mode on students’ writing ability and interest. The results show that: after the experiment, the writing performance of the students in the experimental class has been significantly improved compared with that of the students in the control class, and the interest and enthusiasm of the experimental class in writing have been significantly improved. Therefore, it is concluded that the Scaffolding Instruction mode can improve primary school students’ English writing ability and interest.